2011
DOI: 10.1016/j.ijid.2011.04.015
|View full text |Cite
|
Sign up to set email alerts
|

Acute melioid community-acquired pneumonia

Abstract: Physicians in melioidosis endemic areas should administer antimicrobials covering B. pseudomallei to patients with CAP who visit the ED during the rainy season, who have poor sugar control with glycemia ≥250mg/dl, and who are in shock on ED arrival, to facilitate timely, appropriate antibiotic therapy and lower the mortality rate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
7
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 20 publications
3
7
0
Order By: Relevance
“…The top 24 global EM articles for 2011 are listed in Table 3 2–25 . The complete database of all 206 global EM articles for 2011, as well as full summaries and critical analyses of the top 24 global EM of articles of 2011, can be found online as Data Supplements S1 and S2 (available as supporting information in the online version of this paper).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The top 24 global EM articles for 2011 are listed in Table 3 2–25 . The complete database of all 206 global EM articles for 2011, as well as full summaries and critical analyses of the top 24 global EM of articles of 2011, can be found online as Data Supplements S1 and S2 (available as supporting information in the online version of this paper).…”
Section: Resultsmentioning
confidence: 99%
“…They note that the presence or absence of plasma leakage remains an important factor in directing treatment for patients with Dengue fever. Kung et al 18 analyzed a series of cases of acute myeloid community‐acquired pneumonia in Taiwan. The following factors were predictive of myeloid‐type pneumonia: presentation during the rainy season, poor glycemic control, and shock on arrival.…”
Section: Discussionmentioning
confidence: 99%
“…Our previous matched care-control study comparing patients with melioidosis pneumonia and those with nonmelioid CAP showed that visiting the ED during the rainy season, poor control of glucose levels, and arriving in the ED in shock were independent risk factors for patients with CAP caused by B pseudomallei. 16 Currie and Jacups 17 also indicated that heavy rainfall in the 14 days before admission was an independent risk factor for pneumonia, septic shock, and death in patients with melioidosis. It is postulated that heavy rainfall with strong winds brings buried B pseudomallei isolates to the soil surface; thereafter, they are more likely to be inhaled at high concentrations causing pneumonic melioidosis; this may result in the increased severity associated with septic shock and early mortality.…”
Section: Discussionmentioning
confidence: 97%
“…21 However, we found that the early mortality rate of our patients with acute melioidosis pneumonia was 56%, which is much higher than that observed for both patients with CAP in the ED (2.5%) 22 and patients with nonmelioid CAP (18.3%) in our previous study. 16 The current recommended antimicrobial agents and dosages for CAP are not active against B pseudomallei in vitro. 2 A specific guideline for CAP that is caused by B pseudomallei is needed in addition to a locally adapted guideline for CAP treatment in an endemic area.…”
Section: Discussionmentioning
confidence: 99%
“…In some cohorts, inhospital mortality approaches 60%. 103 Unfortunately, early mortality (<48 hours) can also be high (above 40%), 103 hence clinical suspicion and use of adjunctive nonculture based tests are key to ensuring timely therapeutic treatment.…”
Section: Pulmonary Melioidosismentioning
confidence: 99%